A Comparative Study between Early Versus Delayed Laparoscopic Cholecystectomy for Acute Cholecystitis in a Tertiary Care Center of Nepal - Ashok Koirala; Ram Sagar Shah; Sachidanand Shah; Dinesh Adhikari; Amit Bhattarai; Richa Niraula; Ajay Kumar Yadav (Journal of Nobel Medical College, 2022)
Background: Laparoscopic Cholecystectomy is considered as a gold standard treatment for symptomatic cholelithiasis. The timing of surgery for acute Cholecystitis is still controversial, weather to go early surgery or wait for six to eight weeks after conservative management. Therefore, the aim of this study is to compare the clinical outcomes of early versus delayed laparoscopic cholecystectomy for acute Cholecystitis.